Polycystic Ovaries and Associated Clinical and Biochemical Features in Young Women - Farah Naz Tahir, Shumaela Kanwal, Muhammad Safdar, Aqsa Arif Malik, Sahar Hakim, Muhammad Naim Ashraf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aetiology of polycystic ovarian syndrome (PCOS) is unknown, even though it is the most frequent endocrine disorder in women of reproductive age. Previous community-based studies were unable to directly estimate the prevalence of PCOS in these communities since they did not conduct comprehensive biochemical and clinical screening. Objective: This research focused on polycystic ovaries and associated clinical and biochemical features in young women. Study Design: Cross-sectional study Study Setting: This study was conducted in Department of Biochemistry Central Park Medical College, Lahore from 1st August 2022 1st February 2023. Methodology: During the study period, volunteers were recruited from hospitals and requested their consent. While women were informed specifically that ovaries scan (ultrasound) would be used to detect polycystic ovaries. After the confirmation of polycystic ovaries, they were taken 201 as a case group. To compare the data, we also recruited 233 healthy participants as a control group. After taking consent and filling the questionnaire both cases and controls participants were requested for biochemical and hormonal analysis. SPSS version 20 was used for data analysis. Results: The mean age of control 25.83 ± 4.6 years and 27.12 ± 5.52 years of with significantly increased BMI in the women with PCO as compared to controls (p = 0.001). Insulin and resistance are significantly increased in those women suffering from PCO. LH, oestradiol are significantly increased and FSH is significantly decreased in cases as compared to control. The level of testosterone is not significant in this cohort. SHBG and also free testosterone index are also not significantly different. Practical implication: Even though many women in rural areas experience signs of a disease, they are hesitant to see a gynecologist or endocrinologist for treatment due to a lack of disease awareness, management, and medical therapy that conforms to criteria. Most patients don’t get treatment because of this hesitation, which can cause a host of problems down the road. This study was done to better understand the clinical and biochemical characteristics of polycystic ovary syndrome in young women. Conclusion: Most women with infertility in Pakistan’s leading medical centers have polycystic ovaries. Women with polycystic ovaries may not always experience the symptoms of polycystic ovarian syndrome. However, 26 percent of women in this research had PCOS. Women with polycystic ovaries often have hyperinsulinemia and high levels of insulin resistance. While LH and FSH are both considerably higher in cases than in controls, they are unrelated. The results of this investigation showed that although testosterone levels did not influence PCO, a negative correlation between insulin levels and SHBG hormone was seen in individuals with elevated insulin. Hence, the management of insulin can reduce the risk of PCO. Keywords: PCO, PCOS, LH, FSH, oestradiole, hyperinsulinemia, HOMA-IR